Higher Prevalence of PldA, a Pseudomonas aeruginosa Trans-Kingdom H2-Type VI Secretion System Effector, in Clinical Isolates Responsible for Acute Infections and in Multidrug Resistant Strains - Boulant, Thibaud; Boudehen, Yves-Marie; Filloux, Alain; Plesiat, Patrick; Naas, Thierry; Dortet, Laurent (Frontiers in Microbiology, 2018)
Pseudomonas aeruginosa can manipulate eukaryotic host cells using secreted effectors delivered by the type III or the type VI Secretion Systems (T3SS and T6SS). The T3SS allows the injection of bacterial effectors (Exo toxins) into eukaryotic cell. P. aeruginosa, encodes three T6SSs, H1-, H2- and H3-T6SS. The H1-T6SS is mainly involved in delivering toxins to kill bacterial competitors. Recently, two T6SS-secreted phospholipases D, PldA (H2-T6SS) and PldB (H3-T6SS), were identified as trans-kingdom virulence effectors, triggering both killing of bacterial competitors and internalization into non-phagocytic cells. We deciphered the prevalence of T3SS and T6SS effectors encoding genes in 185 clinical isolates responsible for infections (septicaemia, pulmonary infections, urinary tract infections and chronic infections in CF patients), 47 environmental strains, and on 33 carbapenemase-producers. We included 107 complete genomes of P. aeruginosa available in public databases. The prevalence of pldA is increased in clinical isolates responsible for severe acute infection and particularly in multi-drug resistant strains. In contrast, the pldB prevalence was high (96.8%) in all isolates. Regarding T3SS effectors, exoT and exoY are present in nearly all isolates while exoS and exoU were found to be exclusive with a higher prevalence of exoU+ strains in severe acute infections. The hypervirulent exoU+ isolates are more prone to be pldA+, suggesting a role of PldA in virulence. Finally, we observed that extremely-drug resistant isolates producing an IMP-type carbapenemase were all pldA+. Our results suggest that PldA might have a role during pulmonary infections and have been co-selected in multidrug resistant strains particularly IMP-producers.